(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This research aims to examine the ability of impact of the cash flow statement indicators in the change in the market value of the industrial firms listed on the Palestine Stock Exchange. The research population consisted of (13) firms during the period (2015-2020). Data were collected from the annual financial statements of the firms. The research relies on the Pooled effects model to analyze the cross-section data (Panel Data), and the multiple regression method to test the hypotheses. The research finds a positive significant impact of (the ratios of cash flows from operating activities to sales, the return on assets from operating cash flows, and cash flows from operating activities to total current liabilities) in the change in the market value. Also, the impact of the return on equity from operating cash flows on the change in market value ratio was negative. In contrast, there was no significant impact of the dividends and the cash flows from operating activities to total liabilities ratios on the change in the market value. The research recommends the need to pay attention to the indicators of the cash flow statement to improve the managerial investment decisions.